Q-Analysis Methods for the Simultaneous Spectrophotometric Estimation of Levofloxacin Hemihydrate and Ornidazole in Tablet Dosage Form - Kumar, Rekha Rajeev; Kumar, P Rajeev (Stamford Journal of Pharmaceutical Sciences, 2011)
Key words: Levofloxacin; Ornidazole; UV-spectrophotometry; Q-Analysis DOI: http://dx.doi.org/10.3329/sjps.v3i2.8032 S.J. Pharm. Sci 3(2): 16-19